2020
DOI: 10.3390/molecules25173930
|View full text |Cite
|
Sign up to set email alerts
|

New Arctic Bacterial Isolates with Relevant Enzymatic Potential

Abstract: Fragments of wood drifting in the vicinity of Spitzbergen were used for the isolation of microorganisms, carried out using atypical carbon sources: colloidal chitin, cellulose and carboxymethylcellulose, xylan, casein, tributrin and olive oil. Purified cultures were subjected to a three-step identification: with classical methods, using MALDI-TOF MS Biotyper whole-cell protein fingerprinting, and molecular analysis of 16S rDNA. Subsequently, a preliminary assessment of the enzymatic potential of isolates was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, that bacterial species isolated from MPs in this study were previously found in both cold and non-cold environments, while most of the isolated bacterial species were similar to those found in other types of samples from cold polar and non-polar regions. For example, other researchers isolated Shewanella baltica [ 58 ], Pseudomonas lundensis [ 59 , 60 ], Pseudomonas leptonychotis [ 61 ], Carnobacterium funditum [ 62 ], Carnobacterium iners , Flavobacterium degerlachei [ 63 ], Arthrobacter agilis [ 64 ], Micrococcus luteus [ 21 ], and Leifsonia rubra [ 14 , 65 ] from water, soil, and animal samples of polar origin. The species Pseudomonas lundensis , Pseudomonas peli [ 25 ], Acinetobacter lwoffii [ 66 ], Sporosarcina globispora [ 67 ], Carnobacterium inhibens [ 68 ], Arthrobacter alpinus [ 69 , 70 ], and Arthrobacter agilis were isolated from cold non-polar environments such as frozen food, non-polar permafrost sediments, glaciers, glacial currents, a subglacial lake in the Himalayas, and Siberian permafrost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, that bacterial species isolated from MPs in this study were previously found in both cold and non-cold environments, while most of the isolated bacterial species were similar to those found in other types of samples from cold polar and non-polar regions. For example, other researchers isolated Shewanella baltica [ 58 ], Pseudomonas lundensis [ 59 , 60 ], Pseudomonas leptonychotis [ 61 ], Carnobacterium funditum [ 62 ], Carnobacterium iners , Flavobacterium degerlachei [ 63 ], Arthrobacter agilis [ 64 ], Micrococcus luteus [ 21 ], and Leifsonia rubra [ 14 , 65 ] from water, soil, and animal samples of polar origin. The species Pseudomonas lundensis , Pseudomonas peli [ 25 ], Acinetobacter lwoffii [ 66 ], Sporosarcina globispora [ 67 ], Carnobacterium inhibens [ 68 ], Arthrobacter alpinus [ 69 , 70 ], and Arthrobacter agilis were isolated from cold non-polar environments such as frozen food, non-polar permafrost sediments, glaciers, glacial currents, a subglacial lake in the Himalayas, and Siberian permafrost.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that bacteria in Antarctic meltwater ponds are important for driving biogeochemical cycles, sustaining essential chemical processes, and participating in a carbon sink and because they are able to tolerate environmental fluctuations, studying them could be especially useful for understanding environmental and ecological changes in Antarctica as well as discovering new microbial cell factories for modern biotechnology and biorefinery applications. For example, biotechnologically attractive enzymes (e.g., proteases, lipases, amylases, ureases, nucleases, β-galactosidases, and keratinases) [ 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and pigments (e.g., carotenoids) [ 19 , 26 , 27 , 28 , 29 , 30 , 31 ] can be synthesized by culturable psychrophilic and psychrotrophic bacteria [ 32 ].…”
Section: Introductionmentioning
confidence: 99%